Analisis Kinerja Per Connection Classifier dan Failover pada Multiple Gateway Internet Networks - Faris Agil Putra; Alif Subardono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
A good design for the internet network is needed to create a good internet network. The problem that often occurs is the availability of the internet network. A solution that can be applied to this problem is to implement Load Balancing and Failover. The network concept used was Load Balancing with the Per Connection Classifier method and Failover. Load Balancing is a technique used to optimally distribute traffic loads on a network with two or more connections. The method used was the Per Connection Classifier which could group connections. The Failover technique was also applied to the redundancy function. The test scenario would test the distribution of traffic loads, Failover testing, and comparative analysis of QoS with parameters jitter, packet loss, throughput, and delay on the performance of the system with Per Connection Classifier method based on Classifier Both Addresses, Both Ports, and Both Addresses and Ports. The results of the test show that the system is able to distribute the traffic, the system can create redundancy, while for overall QoS testing, Both Addresses gets better performance than other classifiers.